What's New in Osteogenesis Imperfecta? - Parry, Nicola (MD Conference Express, 2013)
This article discusses the pathophysiology of osteogenesis imperfecta (OI), in particular in relation to some rare, recessive forms of the condition. Although historically considered a collagen-related condition, predominantly due to mutations in genes that encode the alpha chains of collagen type I, mutations in various noncollagenous genes have also more recently been discovered to cause some forms of OI.